A study to compare the functional outcome of anterior cruciate ligament reconstruction using autologous tendon graft with or without platelet rich plasma augmentation - Sharma, Vikas; Assat, Rajendra Prasad; Tiwari, Bikash Kumar; Samaria , Kartik (International Journal of Research in Orthopaedics, 2025)
Background: Reconstructing the anterior cruciate ligament (ACL) poses significant challenges, particularly in achieving secure attachment between the tendon and bone. Bone integration within the bone tunnel determines the outcome, influenced by graft type and fixation method. Platelet rich plasma (PRP) may enhance the ligamentization process of the graft, facilitating improved incorporation within bone tunnels. This synergistic approach could mitigate tunnel enlargement and graft failure over time. Methods: A prospective comparative study (August 2023-June 2024) involved 80 patients (18-45 years) with acute complete ACL tears. Patients were divided into two groups: Group A (n=40) received 6 ml PRP injection during arthroscopic ACL reconstruction, while Group B (n=40) underwent surgery without PRP. Follow-ups occurred at 6 weeks, 3 months, and 6 months Results: At 6 months, PRP group’s SNQ values indicated improved tendon-bone healing. Lysholm scores showed significant improvements at 3 (14.49%) and 6 months (10.67%) (p<0.05). IKDC scores demonstrated similar trends, with significant differences at 3 (12.67%) and 6 months (7.08%) (p<0.05). Conclusions: The use of PRP improved Lysholm score, IKDC score and SNQ value to certain extent but we did not find any statistically significant benefit in the PRP group.